2022
DOI: 10.1155/2022/5576194
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Simulation of Heat and Mass Transmission in Casson Fluid Flow across a Stretching Surface

Abstract: This research presents a review of an analytical simulation of heat and mass transmission features of steady, non-Newtonian Casson fluid motion across a permeable medium through a stretching surface. The effects of heat production and thermal emission are put into discussion. Mathematically, the governing model is manipulated by a series of nonlinear partial equations, which are then modified into ordinary differential equations with the assistance of appropriate conversion. Analytical results for such equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Concerning the above assumptions, and referring to Casson impacts, ternary hybrid nanofluids model, and magnetic influences, the two dimensional governing equations, i.e. continuity, momentum, and thermal equations, can be appointed as [43,55,56…”
Section: Problem Formulation and Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the above assumptions, and referring to Casson impacts, ternary hybrid nanofluids model, and magnetic influences, the two dimensional governing equations, i.e. continuity, momentum, and thermal equations, can be appointed as [43,55,56…”
Section: Problem Formulation and Equationsmentioning
confidence: 99%
“…review work illustrates a survey of various numerical techniques appropriate to Casson fluid by examining different kinds of research articles, which were investigated by Verma and Mondal [42]. Khan et al, [43] presented an examination of an analytical-numerical of heat and mass transmission characteristics of steady, non-Newtonian Casson fluid over a stretching surface. El-Sayed et al, [44] and Yasin et al, [45] investigated mixed convection in Casson nanofluid around horizontal cylinder and solid sphere.…”
Section: Introductionmentioning
confidence: 99%
“…In this line, Khan et al 11 provided a numerical analysis of heat transfer and mass transfer for unstable boundary flow in the Casson fluid. Khan et al 12 reported analytical modeling of the heat and mass transfer phenomena of Casson fluid through a starching surface. Khan et al 13 recently found a similar phenomenon for the Williamson magnetohydrodynamics (MHD) flow.…”
Section: Introductionmentioning
confidence: 99%
“…Mohamed et al, [24] examined effects of slip on boundary layer flow and heat transmission on a horizontal flat surface submerged in Casson ferrofluid based on blood. Numerical analysis is done on the magnetite and cobalt ferrite ferroparticles suspended in the Casson fluid, which is analogous to human blood K A Khan et al, [25], in their study found that the model has been enhanced to predict high shear-rate viscosities even when there is a dearth of additional shear-rate data. Mukhopadhyay et al, [26] studied the Casson liquid flow on various surfaces taking into account different influencing factors.…”
Section: Introductionmentioning
confidence: 99%